Penggunaan Permainan Lego Untuk Meningkatkan Kemampuan Sosial Emosional Anak Usia 4-5 Tahun Di Kb Paud Darut Tauhid Menemeng - Saopiati; Sudirman; Budiman (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2024)
The objectives of this study are 1). To find out the implementation of lego games in improving the social-emotional of children aged 4-5 years in kb darut tauhid menemeng, 2). Knowing how to play lego games in improving the social-emotional of children aged 4-5 years at kb darut tauhid menemeng, 3). Knowing the supporting and inhibiting factors of teachers in the use of lego games in improving the social-emotional of children aged 4-5 years at kb darut tauhid menemeng. This research uses a qualitative approach with the type of field research (field research), data collection procedures using observation, interview and documentation methods. Data analysis used is data collection, data reduction, data display and verification and confirmation of conclusions. The results showed that the implementation of the use of lego games in improving the social-emotional of early childhood in kb darut tauhid menemeng went well. This is evidenced by the teacher guiding and teaching students well and positively starting from welcoming, opening, core, and closing activities. The method used is by arranging by color, making lego towers, lego bowling, making shapes from the surroundings, hunting for lego pieces, playing guessing shapes and role play or role play. The supporting factors for the use of lego games to improve children's social emotions include the media, the size of the room and teachers who encourage and motivate students to always be enthusiastic. The obstacles to the use of lego games to improve children's social-emotional include students not being able to make buildings and the media used.